MOLECULAR STUDY OF THE RED-LEGGED HAM BEETLE NECROBIA RUFIPES (DE GEER, 1775) (COLEOPTERA: CLERIDAE) FROM THE ERBIL PROVINCE OF THE KURDISTAN REGION, IRAQ - H. M. Muhammad; P. A. Jalil; N. A. Mawlood; K. M. Taha (مجلة الأنبار للعلوم الزراعية)
Necrobia rufipes (Coleoptera: Cleridae) are economically essential since most species are predaceous on other insects in both adult and larval stages. Molecular investigation is useful for identifying species and other downstream analysis. In addition to identification, this research addresses past gaps in knowledge through establishing the sequence of current insect COX genes and other investigations. A novel method was developed in this study to examine COX gene sequencing and to determine the relationship between Cleridae subfamilies. The DNA was isolated, and a band of 550 bp of the mt COX gene was amplified. Then the amplicons were sequenced. Parts of the COX gene were aligned with Clustal Omega and visualized and edited via Jalview software. This research presented the Ts:Tv mutation ratio through a sequencing technique for the species with reliable results. The species from the Kurdistan region in this study were clustered in a monophyletic clade published in Germany (KU916741.1) with a high identity value (100%). The COI sequence of the species was submitted to GenBank with the PP175929.1 accession number. The base composition of the COX gene sequence had a higher AT figure at 67.89% compared to the GC’s 32.1%. These results offer new valuable insights on the Necrobia rufipes and may provide useful data for its identification, bioinformatics uses, and management applications. The results show that the mt-COX can be used as a marker for further molecular experiments.